HEALTH CARE RESOURCES ORGANISATION·AS A DETERMINANT OF UTILIZATION OF PUBLIC HEALm FACILITIESAMONGRETIRED CIVILSERVANTSINDELTA STATE - Nabofa, O.E. (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2023)
Health promotion efforts should also be directed at retired civil servants since they constitute a large proportion of the populace. These efforts should start with the determination of the extent to which healthcare resources organisation is affecting healthcare services utilisation by the retired civil servants. This study was therefore carried out to find out if existing healthcare resources organisation would determine utilization of public health facilities among retired civil servants in Delta Central Senatorial District. The descriptive survey research design of the ex-post/acto type was adopted to study a total population of 4,575 (males = 2, 070 males and females = 2, 505) retired civil servants listed on the Delta State Pensions Management Board as retirees from Delta Central Senatorial District of Delta State. The purposive sampling technique was used to draw a representative sample size 0/400 participants. A validated self-structured questionnaire titled "Healthcare Resource Organisation as a Determinant o/Utilization of Public Health Facilities among Retired Civil Servants Questionnaire (HRODUPHFQ)" with a Chrombach alpha reliability coefficient 0/0.89 was used to collect data/or this research. Obtained data were analysed using multiple regression analysis. Results showed that existing healthcare resources organisation negatively predict utilisation of public health facilities among retired civil servants in Delta Central Senatorial District. It was concluded that the current organisation of healthcare resources may not be suitable for Utilization of Public Health Facilities among retired civil servants in Delta State. Based on the findings of this study, it was recommended that there is need to rearrange the organisation of our healthcare resources so as to make them more suitable for utilisation by retired civil servants.